2013
DOI: 10.1177/2050640613500266
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the speed of food intake on multichannel impedance in patients with gastro‐oesophageal reflux disease

Abstract: This first study addressing the effect of eating speed on reflux episodes in GORD patients did not support the general belief that reflux increases following fast eating. Acid and non-acid reflux were similar at the first postprandial hour, then acid reflux episodes were predominantly higher, which implicate the importance of acid pockets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Third, we investigated acidic reflux events only by Bravo pH monitoring. In a recent study, we showed that number of acid reflux episodes decreases while non‐acid reflux episodes increase one hour after meals 25 . Twenty‐four‐hour impedance‐pH monitoring was another option to detect weak and non‐acid refluxes since patients were asked to have intercourse two hours following the meal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we investigated acidic reflux events only by Bravo pH monitoring. In a recent study, we showed that number of acid reflux episodes decreases while non‐acid reflux episodes increase one hour after meals 25 . Twenty‐four‐hour impedance‐pH monitoring was another option to detect weak and non‐acid refluxes since patients were asked to have intercourse two hours following the meal.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we showed that number of acid reflux episodes decreases while non-acid reflux episodes increase one hour after meals. 25 Twenty-four-hour impedance-pH monitoring was another option to detect weak and non-acid refluxes since patients were asked to have intercourse two hours following the meal. However, it would not be physiologically feasible to perform sexual activity with a catheter-based system for volunteers, and the likelihood of non-acid reflux producing a different symptom profile might be lower than acidic reflux in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Fast (within 5 min) and slow (within 30 min) eating were compared in 46 patients with GERD and no statistical significant difference in total reflux events was revealed within 3 h of ingestion [18]. Another study in 60 patients with GERD also showed no statistical difference in terms of the total reflux events, total reflux time, and reflux symptoms within 3 h among patients with normal or abnormal pH monitoring when comparing fast (within 5-10 min, mean 8.4 min) and slow eating protocols (within 25-30 min, mean 27.7 min) [19]. Additionally, no significant difference in the total reflux events and time was found in a recent study of 26 GERD patients with obesity (BMI > 30 kg/m 2 ) [20].…”
Section: Eating Speedmentioning
confidence: 91%
“…Rapid food intake was assumed to increase reflux as well [ 38 ]. However, two controlled trials showed no difference between fast- and slow-eating groups regarding either the number of reflux episodes or the severity of symptoms [ 39 , 40 ]. Shorter dinner-to-bed time has been identified as a risk factor for GERD [ 41 ].…”
Section: Dietary Modificationmentioning
confidence: 99%